Assessment of the shock adsorption properties of bike helmets: a numerical/experimental approach. Issue 5 (3rd April 2020) - Bocciarelli, Massimiliano; Carvelli, Valter; Mariani, Stefano; Tenni, Matteo
Abstract: In this paper, a numerical and experimental study of the shock absorption properties of bike helmets is presented. Laboratory compression and tensile tests were carried out on samples of expanded polystyrene (EPS) and polycarbonate (PC), respectively constituting the internal shock absorption layer and the external hard shell of composite helmets. The measured responses of the two materials were then exploited to calibrate the relevant elasto-plastic constitutive models, adopted in full-scale finite element analyses of a helmet subject to standardized impacts. The simulations allowed assessing the time evolution of the acceleration measured inside the headform (according e.g., to EN 1078) and the failure mechanisms of the helmet, if any, as induced by the localization of plastic deformations.